Analisis kemampuan membaca pemahaman ditinjau dari minat belajar pada peserta didik kelas 5 sekolah dasar - Cahyaningsih, Ayu; Rukayah, Rukayah; Kamsiyati, Siti (Universitas Sebelas Maret, 2021)
Reading become the most important aspect of Bahasa Indonesia learning because reading is some activity that implicate visual activity start from translating until understanding the poin of the text. The good comprehension reading capability is when someone competent to understanding the content of the text. There are some indicators to measure the comprehension reading capability. Comprehension reading capability should be implemented to elementary school studentespecially at grade V. Basic competency that demand the student to understand and analysis the text need to use the comprehension reading capability. Obstacle that happen frequently are students that have less interest about a text. This low interest to learn a text make them have a low comprehension reading capability. Research to Djama’atul Ichwan elementary school students at grade V represent that their comprehension reading capability are good enough seen from the high study interest. With thath high study interest and high effort will get the good comprehension reading capability.